Cultural representation and cultural studies - Zhou, Xian, 1954- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"From the perspective of critical cultural sociology, this book delves into the intertwining relations of cultural transformation and social evolution, illuminating contemporary Chinese culture's landscape and underlying logic since the 1980s. With a special focus on the tensions among politics, economy, and culture itself, the book examines the transitions of Chinese culture from tradition to the modern age. It expounds the cultural differentiation and its effect in contemporary China. Within this framework, the author addresses some key issues and phenomena that figure in the cultural scene of modern China, ranging from the crisis of Chinese cultural identity in the context of globalization, the media culture and its impacts on everyday life, to the visual culture and social transformation. Offering a panoramic view of Chinese contemporary culture, literature, arts, and society, this title will serve as an essential read for scholars of China Studies, Cultural Studies, and Visual Culture as well as anyone interested in what's going on in Chinese contemporary culture"--
Translation of: Wen hua biao zheng yu wen hua yan jiu.
Keywords: Aesthetics, Chinese -- 20th century; China -- Civilization -- 20th century; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Popular Culture